2013
DOI: 10.4236/aces.2013.32017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Curing Poly(<i>p</i>-Phenylene Sulfide) on Thermal Properties and Crystalline Morphologies

Abstract: Commercial poly(p-phenylene sulfide) (PPS) was thermally cured, which resulted in an increase of molecular weight due to cross-linking. Non-isothermal crystallization studies of samples cured for up to 7 days at 250˚C showed a monotonous increase of crystallization temperature compared to pure PPS. However, a further increase of curing time decreased the crystallization temperature. The change in the half-crystallization time (t 1/2 ) was similar to the crystallization temperature. Thus, the cross-linking of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 10 publications
4
10
0
Order By: Relevance
“…It is observed that PPS without thermal oxidation treatment was completely dissolved in the solvent, while PPS after treatment had a gel content of 1.8% as shown in Table . This result demonstrates that an effective cross-linking structure could only be formed by a prolonged high-temperature treatment, and this result also verified that the oxidized functional groups formed even by melt processing in a short time. The obtained cross-linking structure then greatly improves the elasticity of the PPS melt and provides a prerequisite for the formation of stable bubbles in the subsequent foaming process.…”
Section: Resultssupporting
confidence: 57%
“…It is observed that PPS without thermal oxidation treatment was completely dissolved in the solvent, while PPS after treatment had a gel content of 1.8% as shown in Table . This result demonstrates that an effective cross-linking structure could only be formed by a prolonged high-temperature treatment, and this result also verified that the oxidized functional groups formed even by melt processing in a short time. The obtained cross-linking structure then greatly improves the elasticity of the PPS melt and provides a prerequisite for the formation of stable bubbles in the subsequent foaming process.…”
Section: Resultssupporting
confidence: 57%
“…DMA results showed a corresponding increase in the temperature location of the dissipation peak and a decrease in its amplitude when T α increased above 100°C. Similarly, Lee et al [21] investigated commercial PPS by thermal curing and they found an increase of molecular weight due to crosslinking. They concluded the crosslinking of PPS affected crystallization behaviors significantly.…”
Section: Introductionmentioning
confidence: 95%
“…This is because the linear or branched molecular structures of thermoplastics become more brittle during thermal aging [ 36 ]. Researchers attributed this to the cross-linking and crystallinity, which depended on the temperature and the exposure time, as reported by Zhang et al [ 37 ] and Lee et al [ 38 ]. Molecular chain scission, post-crosslinking, and crystallinity increment also occur in the GF/PPS composite samples during thermal aging [ 39 ].…”
Section: Resultsmentioning
confidence: 83%